BUDIDAYA TANAMAN KANGKUNG DAN IKAN NILA DENGAN SISTEM AKUAPONIK DEEP FLEW TECHNIQUE SEBAGAI KETAHANAN PANGAN DI WILAYAH PERBATASAN REPUBLIK INDONESIA-REPUBLIK DEMOKRATIK TIMOR LESTE - Suci Andiewati; Mathilde Santos Oliveira; Daniel Candido Da Costa Soares (Jurnal Abdi Insani, 2023)
Aquaponics is an alternative to growing plants, raising fish or incorporating an environmentally friendly aquaculture, hydroponic cultivation system which is a solution to overcome limited land, limited water resources, and increase food security. In this aquaponic system, water spinach plants utilize nutrients from tilapia fish waste. The purpose of this activity is to introduce the aquaponic cultivation system of kangkung integrated with tilapia to members of the Indonesian National Armed Forces security guards at the RI-RDTL border; 2) Increase food security skills by cultivating kale with aquaponic media. This activity was carried out in Belu Regency, East Nusa Tenggara Province in February 2022. The participants numbered 20 members of the TNI security guards at the RI-RDTL border at Atambua City. The method of carrying out activities is by counseling and assisting in cultivation with the deep fly technique aquaponic system. This activity resulted in a population of organic plants that could be planted 10 times more. With aquaponics plants can be grown at high density by floating systems on water. This system can accommodate up to 10 times the number of plants in the same area. The pond produced from this activity is 3X4 meters in size by spreading tilapia seeds. The implementation of community service activities ran smoothly and received a positive response. This can be seen during the discussion and mentoring sessions from members of the TNI security guard at the RI-RDTL border Atambua City who were very enthusiastic about participating in this activity. With the results of the kale vegetable harvest, it can be seen the understanding and skills of members of the TNI security guards at the RI-RDTL border of Atambua City in cultivating kale and tilapia using the aquaponic deep fly technique system.